Prevalence and identification of subclinical mastitis in cows at BLRI Regional Station, Sirajganj, Bangladesh - Kabir, Md. Humayun; Ershaduzzaman, Md.; Giasuddin, Md.; Islam, Md. Rafiqul; Nazir, K. H. M. Nazmul Hussain; Islam, Mohammed Sirajul; Karim, Md. Rezaul; Rahman, Md. Hafizur; Ali, Md. Yousuf (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The study was conducted to assess the prevalence of subclinical mastitis in dairy cows at Baghabari milk shed area of Sirajganj and Pabna districts in Bangladesh. Materials and methods: A total of 300 milk samples were collected from crossbred dairy cows, and the milk samples were subjected for using California Mastitis Test (CMT). Besides, data related to farm management were taken from 60 farmers through direct interviews. The CMT was compared with White Slide Test (WST) and Surf Field Mastitis Test (SFMT). The samples showing strong positive reaction to mastitis by CMT were used for the isolation of associated bacteria using conventional bacteriological examinations and biochemical properties. The isolated bacteria were subjected for antibiogram studies by disc diffusion method. Results: Out of 300 samples, 153 (51%) revealed positive reactions denoting that the cows were suffering from subclinical mastitis. Of the 153 samples, 39(13%) were trace-positive, 56(18.56%) were weak-positive, 33(11%) were distinct-positive, and the rest 25(8.3%) samples were strongly positive. In comparison economically among CMT, WST and SFMT, SFMT was found to be the cheapest and easiest. In this study, the cows were mostly infected with mixed infection with Staphylococcus spp., Streptococcus spp., Escherichia coli, Salmonella spp., and some cows had single bacterial infection. It was observed that most of the microorganisms were sensitive to Gentamycin, Amoxicillin and Ceftriaxone, and were resistant to Penicillin, Ciprofloxacin and Colistin sulphate. Conclusion: Overall prevalence of subclinical mastitis in the crossbred dairy cows at Sirajganj and Pabna district is 51%. It indicates that subclinical mastitis is a major threat for dairy industry in the studied areas. Early detection and appropriate preventive measures are suggestive to successful control of the disease. http://doi.org/10.5455/javar.2017.d227